Two different types of provenances and the amalgamation of subduction complexes in the Eastern Tianshan of the Southern Altaids - Mao, Qigui; Xiao, Wenjiao; Sang, Miao; Ao, Songjian; Song, Dongfang; Tan, Zhou; Wang, Hao; Li, Rui (Frontiers in Earth Science, 2023)
The nature and final closure of the northern Tianshan Ocean have been debated in regard to the eastern Tianshan orogen, southern Altaids. The Kanguer subduction complex of the eastern Tianshan is the key to addressing these issues. In this study, we report new mapping, geochemical and geochronological results on the Kanguer subduction complex in the Haluo area. Our new results show that upper Permian (257 Ma) basaltic blocks emplaced in a sandstone matrix in the northern HL area are fragments of normal-mid-ocean-ridge-basalt (N-MORB)-type oceanic crust. The geochronological results indicate that the sandstone matrices display two different types of provenances. The first type in the northern part of the cross-section (till Sample YY12) has maximum depositional ages ranging from 316 Ma to 238 Ma. Their depositional settings varied from intraoceanic island arcs to continental Andean arcs after ca. 244 Ma, their detrital zircon age patterns vary from a single peak to multiple peaks, and their zircon ꜪHf (t) values vary from uniquely high positive to some negative values. The second type is in the southern part of the cross-section with Samples YY12 to 21Kg05, which have geochemical signatures of continental island arc sandstone, multiple-peak detrital zircon-age patterns, and positive to negative zircon ꜪHf (t) values. The youngest sandstone sample has a maximum depositional age of 241 Ma. The above provenance results indicate that all mélanges and coherent units north of Sample YY12 belong to an accretionary complex of the Dananhu intraoceanic arc, and those south of Sample YY12 belong to an accretionary complex of the Yamansu-central Tianshan arc. According to the youngest components in both accretionary complexes, which suggest the latest subduction events, we conclude that the final amalgamation timing was after 238 Ma and that the Paleo-Asian Ocean closed in the Middle to Late Triassic.